Effects of exercise on the immune system: overtraining effects on immunity and performance in athletes - MacKinnon, L. T. (Immunology & Cell Biology, 2000)
Overtraining is a process of excessive exercise training in high-performance athletes that may lead to overtraining syndrome. Overtraining syndrome is a neuroendocrine disorder characterized by poor performance in competition, inability to maintain training loads, persistent fatigue, reduced catecholamine excretion, frequent illness, disturbed sleep and alterations in mood state. Although high-performance athletes are generally not clinically immune deficient, there is evidence that several immune parameters are suppressed during prolonged periods of intense exercise training. These include decreases in neutrophil function, serum and salivary immunoglobulin concentrations and natural killer cell number and possibly cytotoxic activity in peripheral blood. Moreover, the incidence of symptoms of upper respiratory tract infection increases during periods of endurance training. However, all of these changes appear to result from prolonged periods of intense exercise training, rather than from the effects of overtraining syndrome itself. At present, there is no single objective marker to identify overtraining syndrome. It is best identified by a combination of markers, such as decreases in urinary norepinephrine output, maximal heart rate and blood lactate levels, impaired sport performance and work output at 110% of individual anaerobic threshold, and daily self-analysis by the athlete (e.g. high fatigue and stress ratings). The mechanisms underlying overtraining syndrome have not been clearly identified, but are likely to involve autonomic dysfunction and possibly increased cytokine production resulting from the physical stress of intense daily training with inadequate recovery. Immunol Cell Biol 2000 Oct;78(5):502-9